ESTABLISHING AN INTERNATIONAL SCHOOL IMAGE IN EAST BEKASI: THE ROLE OF COMMUNITY RELATIONS AT KINDERFIELD HIGHFIELD SCHOOL BEKASI - Gracia, Fransisca; Sarasati, Fitri; Dwijayanti, Risqi Inayah; Yulisinta, Florence; Rakhmania, Raisa (ASPIRATION Journal, 2022)
The significance of education in the contemporary world cannot be overstated, as it plays a pivotal role in shaping a high-quality society. Exploring the theory of Excellence in Public Relations is at the heart of this research. The study delves into the intricate dynamics between organizations and their communities, examining the various communication functions and objectives that underpin these relationships. This study employs a post-positivist paradigm, adopting a qualitative approach and a case study methodology. The author conducts observations, interviews, and documentation to gather information about the individuals involved. The research was conducted through the presentation of data and the formulation of conclusions. The findings indicated that this study applied three specific models, namely Public Information, Two Way Symmetric, and Two Way Asymmetric, out of the four models proposed by the theory. Public relations effectively communicated with the community through various activities such as charity events, open house events, and blood donation events. The research concludes that Kinderfield's community relations activities, conducted by its Public Relations department, have resulted in a positive image for Kinderfield. This achievement has led to the establishment of Kinderfield as a trustworthy school in the eyes of the community, making it a preferred choice for parents seeking an educational institution for their children.